2007
DOI: 10.1590/s0066-782x2007001300008
|View full text |Cite
|
Sign up to set email alerts
|

Associação da síndrome metabólica e seus componentes na insuficiência cardíaca encaminhada da atenção primária

Abstract: SummaryBackground: Metabolic syndrome (MS) is characterized by a collection of risk factors that are associated with elevated rates of cardiovascular events and the risk of developing heart failure (HF). In our field, the association of MS in stable chronic HF patients has not been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
2
3
0
2
Order By: Relevance
“…Regarding the atrial fibrillation (11.96%) and kidney failure (9.08%), similar results were observed by Barreto et al 7 , who observed that such conditions contributed to a higher need for hospitalization and increase in mortality among elderly patients with HF 20,21 .…”
Section: The Study By Latado Et Alsupporting
confidence: 78%
“…Regarding the atrial fibrillation (11.96%) and kidney failure (9.08%), similar results were observed by Barreto et al 7 , who observed that such conditions contributed to a higher need for hospitalization and increase in mortality among elderly patients with HF 20,21 .…”
Section: The Study By Latado Et Alsupporting
confidence: 78%
“…The relation between metabolic syndrome and HF, found mainly among females in this study, is similar to the studies of Balieiro et al 22 , who analyzed cardiac insufficiency and metabolic syndrome in rural area, and to that found by Coelho et al 23 , who studied cardiac insufficiency and metabolic syndrome in patients referred from primary medical care.…”
Section: Original Articlesupporting
confidence: 92%
“…It is questionable if all combinations expose the individual to the same cardiovascular risk, and it is suggested that longitudinal studies consisting of expressive samples, able to include a sufficient number of people for each combination, be pursued (16) .…”
Section: Discussionmentioning
confidence: 99%